Nutritional Habits Of Adolescents Studying In Kashmir University (School) - Naila Irshad; Shifa Zahoor (Revista Electronica de Veterinaria, 2023)
During adolescence, a pivotal stage of physical and emotional development, a nutritious diet is essential for establishing a strong foundation of lifelong health and wellness. However, this age group faces a unique challenge: the coexistence of under and over nutrition. As a result, adolescents are considered a high-risk group for nutritional deficiencies. Despite this, there is a significant knowledge gap regarding their dietary patterns, food preferences, and nutritional status. Recent trends indicate a surge in the consumption of high-calorie, low-nutrient foods, particularly through snacking. While snacking can provide essential nutrients, excessive snacking is linked to increased energy intake, sugar consumption, and unhealthy habits like skipping meals. These dietary patterns are closely tied to impaired cognitive function, behavioral issues, mental health concerns, and eating disorders. To address this, our study investigated the dietary habits, food preferences, and eating patterns of urban adolescents attending Model High School, University of Kashmir, to better understand their nutritional needs and inform effective interventions. METHODOLOGY: A study was carried out to assess the nutritional habits of adolescents in the age group of 13-16 years. A total number of 75 adolescents were selected randomly from Model High School, University of Kashmir. RESULT: Majority of the respondents i.e. 78.8% consumed fast foods with 24.3% consuming it daily. Additionally 26.7% consumed packeted salty snacks, followed by chocolates (22.7%) as snacks. Moreover, 52% of the respondents skipped their meals, with lunch being the most frequently skipped meal (26.7%), followed by breakfast (20%). CONCLUSION: It was found that higher proportion of adolescents consumed fast foods and skipped their meals, with lunch being skipped the most frequently skipped meal.